What influences public views on forensic DNA testing in the criminal field? A scoping review of quantitative evidence - Machado, Helena (2019)
Background: Forensic DNA testing is a powerful tool used to identify, convict, and exonerate individuals charged of criminal offenses, but there are different views on its benefits and risks. Knowledge about public views on forensic DNA testing applied in the criminal field is socially valuable to practitioners and policymakers. This paper aims to synthesize quantitative evidence about the factors that influence public views on forensic DNA testing in the criminal field. Based on a systematic search conducted in January 2019, a scoping review was performed, targeting studies presenting original empirical data that were indexed in Web of Science and PubMed. The two authors performed eligibility and data extraction. Results: The 11 studies were conducted mainly in European countries (Italy, Portugal, Serbia, Spain, Switzerland) and the remaining derived from the USA and New Zealand. Non-representative samples were mostly used to explore the benefits and risks of criminal DNA databases, criteria for insertion and retention of DNA samples and profiles, knowledge, willingness to donate a DNA sample, and custody. The value of forensic DNA databases in protecting society from crime was emphasized. Concerns about improper access to forensic genetic data and risks to civil liberties associated with its uses were expressed. The scarce literature on Forensic DNA Phenotyping and familial searching revealed the same trend of positively valuing forensic DNA testing. Only factors related with socioeconomic position were assessed by more than two studies. Results suggested that public views on forensic DNA testing are influenced by the level of education, age, and exposure to law enforcement occupations although not in a straightforward manner. Conclusion: Further empirical research should assess standardized factors related with social and structural levels (e.g., scientific literacy, public trust in the justice system and concerns about victimization or police activity) and be performed in different national jurisdictions to enable generalization and comparison of findings. It is needed to expand empirical studies on public views about the commercialization of forensic science and the use of recent controversial techniques and new transparency and accountability models.